LANDSLIDE RUNOUT DISTANCE PREDICTION BASED ON MECHANISM AND CAUSE OF SOIL OR ROCK MASS MOVEMENT - Muhammad Qarinur (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
Landslide often occurs in tropical hills area, such as Indonesia. Research on landslide hazard evaluation is necessary to decrease the impact in affected and surrounding areas. Empirical-statistical methods can be used to predict landslide run out distance in an effort to avoid the danger of landslide occurrences. This study aims to determine the correlation between landslide run out distance against high, slope, and volume based on mechanisms and causes of soil or rock mass movement. Data mainly from 106 landslides in Indonesia has been analyzed to search for possible correlations and empirical correlations, there are 34 rotational slides, 54 translational slides, 8 debris flows, and 10 rock falls. Analysis begins by studying the characteristics of the data (explanatory data analysis) and then analyzed by using empirical methods such as geomorphological assessment and geometrical approaches. Then the data is processed by simple linear regression and multiple linear regression method using the R software. The results obtained from the analysis of the general empirical equation form of the correlation between height (H) and run out distance (L) is 1.066H1.093, respectively. This results indicate the higher altitude slopes, the greater distance will happen. The results of the analysis correlation between height and run out distance for the type of mass movements for rotational is L=1.346+1.788 H, translational is L=-3.88+1.578H, debris flow is L=0.682H1.29, and rock fall is L=2.223H0.897. This result shows debris flows landslide run out distance is greater than rotational, translational and rock fall. The results of the analysis correlation between height and run out distance of the trigger due to the rain is L=1.267H1.027, and by an earthquake is L=0.574H1.38. This results show run out distance caused by an earthquake is larger than caused by rain. The correlation between the run out distance and volume (V) yields empirical equation which is V=0.772L2.108. This results indicate that greater run out distance is affected by the growing volume of mass movement. The results of the analysis correlation between height and slope (θ) to run out distance is L=1.448H1.062 tan θ-0,482. This results indicate that slope has a significant impact on the value of landslide run out distance.